2022
DOI: 10.3389/fevo.2022.823026
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Soil Properties Following the Establishment of Exclosures in Ethiopia: A Meta-Analysis

Abstract: Community-led watershed development activities, including the establishment of exclosures (areas where both livestock and farming activities are excluded) on degraded communal grazing land, have become a common practice in Ethiopia since the 1990s. However, it is not yet fully understood how these exclosures change soil organic carbon and total soil nitrogen in different soil types and under different agroecologies. A meta-analysis using data gathered from the most relevant peer reviewed articles from Ethiopia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…The afore-cited studies were conducted in limited locations and the results cannot be fully translated to the context of CRV due to differences in biophysical and socioeconomic differences. This was supported by a recent metaanalysis study on the influence of exclosures on improving soil properties (Yakob et al, 2022). This study suggested that such impacts of exclosures vary with site characteristics and exclosure age.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…The afore-cited studies were conducted in limited locations and the results cannot be fully translated to the context of CRV due to differences in biophysical and socioeconomic differences. This was supported by a recent metaanalysis study on the influence of exclosures on improving soil properties (Yakob et al, 2022). This study suggested that such impacts of exclosures vary with site characteristics and exclosure age.…”
supporting
confidence: 61%
“…The major contribution of exclosures to restoring soil carbon could be attributed to increasing organic input from litterfall and root decomposition (Manaye et al, 2019), protecting the constructed soil and water conservation measures from destruction by free grazing reducing soil erosion, and improving soil moisture content (Mekuria et al, 2011). Increased inputs of decomposable organic matter (e.g., herbaceous plants, litterfalls and grasses) enhanced soil nutrient content, contributed to continuous nutrient cycling in the exclosures over years (Mekuria et al, 2007), and improved soil physicochemical properties and the local environment (Yakob et al, 2022). Consequently, SOC and soil total nitrogen stocks in the older exclosure (Abine Germama‐Gallo Hiraphe) improved significantly as compared to its adjacent grazing land.…”
Section: Discussionmentioning
confidence: 99%
“…The Amhara region is topographically divided into the northern and eastern highlands at > 1500 m asl and the western and southern lowlands between 500-1500 m asl. Areas above 2300 m asl fall within the Dega climatic zone, those between 1500-2300 m asl within the Woina Dega climatic zone, and areas below 1500 m asl fall within the Kolla or hot climatic zones 45 . The annual mean temperature for most parts of the region is 15-21 °C; average rainfall ranges from 850 to 1485 mm with the highest rainfall occurring during the summer season (mid-June and ends in early September) but rains also occur from March-May 47 .…”
Section: Methodsmentioning
confidence: 99%
“…The region has two altitude extremes: the Tekeze Gorge, 550 m asl and the Kisad Gudo peak at 3, 935 m asl. The climate is characterized as Kolla (semi-arid) 39%; Woina dega (subtropical) 49% and Dega (temperate) 12% 45 ; the average rainfall is between 450-980 mm. The dominant soil texture type is sandy loam, and all areas are in the moderate runoff hydrological zone 46 (Suppl.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation